Penerapan Media Digital Menggunakan Aplikasi PhET untuk Meningkatkan Keaktifan Siswa dan Nilai Akademik Siswa dalam Pembelajaran Fisika Kelas 11 di SMA Cita Hati Surabaya - Andi Wibowo; Amy Iwani; Saparso Saparso (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
After the Covid-19 pandemic, it caused learning loss impacts on students in several schools. This makes educators have to think hard to increase students' activeness and understanding of concepts as measured through students' academic grades. The aim of this research is to determine the application of digital media using the PhET application in increasing student activity and student academic grades in grade 11 Physics learning at SMA Cita Hati Surabaya. By considering the learning loss that occurs, the advantages of using digital media, namely PhET, the results of relevant previous research, the researcher will conduct Classroom Action Research. This school action research uses the action research method developed by Kemmis and McTaggart. The research results obtained were that the percentage of students who experienced an increase in academic scores in Physics learning in cycle 1 was 67% and in cycle 2 was 62%. The percentage of students who showed activeness in learning Physics in cycle 1 was 89% and in cycle 2 was 100%.